1991
DOI: 10.2737/pnw-gtr-267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a stream channel-type system for southeast Alaska.

Abstract: Bryant, M.D.; Porter, P.E.; Paustlan, S.J. 1990. Evaluation of a stream channeltype system for southeast Alaska. Gen. Tech. Rep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…Coho salmon, Dolly Varden, and steelhead were captured in reaches with gradients above 15% and were generally captured in small step pools. The densities of Dolly Varden and coho salmon fry and parr that we observed were lower than those reported for lower-gradient streams in southeast Alaska (Dolloff 1983;Bryant et al 1991). We did not observe coho salmon spawning in the high-gradient streams of our study, which may contribute to the lower densities of coho fry and parr that we observed.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Coho salmon, Dolly Varden, and steelhead were captured in reaches with gradients above 15% and were generally captured in small step pools. The densities of Dolly Varden and coho salmon fry and parr that we observed were lower than those reported for lower-gradient streams in southeast Alaska (Dolloff 1983;Bryant et al 1991). We did not observe coho salmon spawning in the high-gradient streams of our study, which may contribute to the lower densities of coho fry and parr that we observed.…”
Section: Discussioncontrasting
confidence: 91%
“…Coho salmon were the dominant species in the low-gradient reaches, and this tends to be common in the small streams of southeast Alaska (Dolloff 1987;Bryant et al 1991). More Dolly Varden than coho salmon were captured in the moderate and high-gradient zones.…”
Section: Discussionmentioning
confidence: 99%
“…Process-based classification approaches provide additional insights into potential response to disturbance (Schumm, 1977;Paustian et al, 1992;Whiting and Bradley, 1993;Montgomery and Buffington, 1997). Channel type classification may also provide a method to predict abundance of salmonid populations (Bryant et al, 1991). Our study is limited to channels with depositional, rather than erosional or transportational, characteristics (Schumm, 1977).…”
Section: Approachmentioning
confidence: 97%
“…Their typical location low in the drainage network makes them likely to integrate cumulative effects of disturbances occurring throughout the watershed. These channel types also support anadromous salmonids that may respond to habitat perturbations (Bryant et al, 1991).…”
Section: Approachmentioning
confidence: 99%